2017
DOI: 10.15252/embj.201796463
|View full text |Cite|
|
Sign up to set email alerts
|

Rab35 GTPase recruits NDP52 to autophagy targets

Abstract: Autophagy targets intracellular molecules, damaged organelles, and invading pathogens for degradation in lysosomes. Recent studies have identified autophagy receptors that facilitate this process by binding to ubiquitinated targets, including NDP52. Here, we demonstrate that the small guanosine triphosphatase Rab35 directs NDP52 to the corresponding targets of multiple forms of autophagy. The active GTP-bound form of Rab35 accumulates on bacteria-containing endosomes, and Rab35 directly binds and recruits NDP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…In our hand, LAMP‐1 recruitment to PCV was not affected in Rab41 KO MEFs (Figure S5c). Moreover, previous studies show colocalization of Rab7, 9A, 17, 23, 30, and 35 with GAS‐containing autophagic vesicles (GcAVs), and these Rabs are involved in GcAVs formation, GcAV‐GcAV membrane fusion, and GcAVs maturation (Minowa‐Nozawa, Nozawa, Okamoto‐Furuta, Kohda, & Nakagawa, ; Nozawa et al, ; Yamaguchi et al, ). In our hands, Rab17, 23, 30, and 35 were not recruited to PcAV, indicating differing intracellular fates and autophagic responses of pyogenic‐grouped GAS and mitis‐grouped S .…”
Section: Discussionmentioning
confidence: 96%
“…In our hand, LAMP‐1 recruitment to PCV was not affected in Rab41 KO MEFs (Figure S5c). Moreover, previous studies show colocalization of Rab7, 9A, 17, 23, 30, and 35 with GAS‐containing autophagic vesicles (GcAVs), and these Rabs are involved in GcAVs formation, GcAV‐GcAV membrane fusion, and GcAVs maturation (Minowa‐Nozawa, Nozawa, Okamoto‐Furuta, Kohda, & Nakagawa, ; Nozawa et al, ; Yamaguchi et al, ). In our hands, Rab17, 23, 30, and 35 were not recruited to PcAV, indicating differing intracellular fates and autophagic responses of pyogenic‐grouped GAS and mitis‐grouped S .…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, galectin 8 has been shown to be essential to NDP52 recruitment during Salmonella infection (Thurston et al, ). Because we recently reported that NDP52 recruitment to intracellular GAS is mediated by ubiquitin and Rab35 but not galectin 8 (Minowa‐Nozawa et al, ), the NDP52 recruitment mechanism into invading bacteria differs between bacterial species. In this study, we showed that LAMTOR2 is involved in TAX1BP1 recruitment both to GAS and Salmonella .…”
Section: Discussionmentioning
confidence: 98%
“…The receptors NDP52 and TAX1BP1/CALCOCO3 have been reported to perform both of these functions during Salmonella infection (Tumbarello et al, 2015). We recently reported that the endosome-resident Rab GTPase Rab35 specifically recruits NDP52 to autophagy targets and autophagosomes (Minowa-Nozawa, Nozawa, Okamoto-Furuta, Kohda, & Nakagawa, 2017), but how other autophagy receptors are spatially regulated to target invading pathogens remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that PHB2 and NDP52-MTPAP contribute distinct mitochondrial recognition mechanisms of mitophagy. A small GTPase, Rab35, recruits NDP52 to damaged mitochondria [40]. KD of Rab35 significantly reduced mitophagic flux after valinomycin treatment for 3 h (Fig EV4D), while cells with double KD of NDP52 and Rab35 showed a comparable level of mitophagic flux to cells treated with siRab35 or siNDP52 alone.…”
Section: Ndp52 Interacts With Mtpap and Irrupts Into Mitochondria Indmentioning
confidence: 97%
“…These results indicate that the interaction between NDP52 and MTPAP is not regulated by Rab35 and TBK1. Rab35 and TBK1 are involved in regulating the interaction between NDP52 and ubiquitin [40]; therefore, we presumed that the NDP52-MTPAP interaction and irruption of NDP52 into mitochondria are part of a ubiquitin-independent mechanism. Accordingly, we showed that NDP52ΔLIM-L, a ubiquitin-binding-deficient mutant of NDP52, interacts with MTPAP ( Fig 2F).…”
Section: Ndp52 Interacts With Mtpap and Irrupts Into Mitochondria Indmentioning
confidence: 99%